Measurement of color degree with Dilution method - Miyoshi, Y (Water science and technology : a journal of the International Association on Water Pollution Research, 2002)
A new method, named the "Dilution method", is proposed to express the color of water. This method is based on the idea to define a color degree with the dilution times when it is hard to distinguish any difference between diluted colored water and distilled water as a standard. The Dilution method has the merits of a simple operation and wide applicability to any colored waters. Moreover, the results of the Dilution method are more understandable and sensitive than those of other conventional measurement methods